The Effect Of Liquidity And Profitability On Firm Value In The Pharmaceutical Sub-Sector Listed On The Indonesia Stock Exchange For The Period 2021–2024 - Yuwandi, Feri; Piter, Jhon; Brandlee, Rio (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study was conducted to gain a deeper understanding of how liquidity, as measured by the Current Ratio (CR), and profitability, as measured by Return on Assets (ROA), affect firm value, as measured by Price to Book Value (PBV), in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in 2021–2024. This study used a quantitative method with a multiple linear regression analysis approach. The sample in this study consisted of 13 companies with a total of 52 observations obtained through a purposive sampling technique based on secondary data in the form of financial reports accessed through the official IDX website. The sample represents companies in the pharmaceutical subsector during the study period. The results show that the Current Ratio (CR) and Return on Assets (ROA) has a positive and significant effect on PBV. Simultaneously, CR and ROA also have a significant effect on firm value. This indicates that the level of liquidity and a company's ability to generate profits are important factors in increasing investor perceptions of firm value. These findings indicate that companies need to manage current assets efficiently and improve profitability to increase their market value.